Orange thyme: phytochemical profiling, in vitro bioactivities of extracts and potential health benefits - Silva, Amélia M. (2021)
Orange thyme (Thymus fragrantissimus) is becoming widely used in food as a condiment and herbal tea, nevertheless its chemical composition and potential bioactivities are largely unknown. Thus the objective of this work is to obtain a detailed phytochemical profile of T. fragrantissimus by exhaustive ethanolic extraction and by aqueous decoction mimicking its consumption. Extracts showed high content in rosmarinic acid, luteolin-O-hexuronide and eriodictyol-O-hexuronide; these were the main phenolic compounds present in orange thyme accounting for 85% of the total phenolic compounds. Orange thyme extracts presented high scavenging activity against nitric oxide and superoxide radicals. Both extracts presented significant inhibitory effect of tyrosinase activity and moderate anti-acetylcholinesterase activity. Both extracts showed a good in vitro anti-inflammatory activity and a weak anti-proliferative/cytotoxic activity against Caco-2 and HepG2 cell lines supporting its safe use. Orange thyme is a very good source of bioactive compounds with potential use in different food and nutraceutical industries.